PERTANGGUNGJAWABAN PIDANA PELAKU REVENGE PORN DI INDONESIA: ANTARA CELAH HUKUM DAN URGENSI PERLINDUNGAN KORBAN - Napiah, Ilman; Terranova, Rheyna (Collegium Studiosum Journal, 2024)
This research discusses legal gaps and victim protection efforts in revenge porn cases in Indonesia. Revenge porn involves the dissemination of intimate photos or videos of an individual on the internet without consent, with the intent of retaliation. The lack of specific regulations makes definitions, evidence, and sanctions weak. Articles of the Penal Code, ITE Law, and Anti-Pornography Law are vulnerable to differing interpretations, while the objective elements are insufficient. The CATAHU survey indicates that cases of Gender-Based Violence (GBV), such as revenge porn, have increased significantly during the pandemic. Victims experience psychological trauma and suicide risks. Meanwhile, the law has not ensured adequate protection. The analysis shows the need for regulatory revisions to clarify criminal elements, proof, and sanctions concerning this retaliatory behavior to protect the dignity and privacy of victims. Efforts should focus on strengthening regulations to close legal loopholes. It is hoped that specific regulations on revenge porn crimes will be established, and the latest Penal Code will address these specific objective elements. Additionally, enforcement should include education. However, it is necessary to examine comparative practices and the roles of relevant parties.